PENGARUH MOTIVASI BELAJAR DAN LINGKUNGAN KELUARGA TERHADAP DISIPLIN BELAJAR SISWA SMAN KECAMATAN AUR BIRUGO TIGO BALEH DI BUKITTINGGI - Alex Yohanes Sirait; Bustari Muchtar; Menik Kurnia Siwi (Universitas Negeri Padang, 2018)
Abstract: This study aims to: 1) The Effect of Learning Motivation to the Discipline of learning of high school students in Aur Birugo Tigo Baleh District, Bukittinggi. 2) The Influence of the Family Environment on the Discipline of Learning of Senior High School students in Aur Birugo Tigo Baleh District, Bukittinggi. 3) The Influence of Learning Motivation and Family Environment jointly affects the discipline of learning of high school students in Aur Birugo Tigo Baleh District, Bukittinggi. This research is a type of associative descriptive study. The population in this study were were SMAN students in Aur Birugo Tigo Baleh sub-district in Bukittinggi. Sampling techniques using purposive sampling. Then use the Slovin formula, so that a sample of 317 people is obtained. Data collection techniques using primary data in the form of questionnaires. For data analysis used multiple regression analysis using the SPSS program. The results showed that: Variable Motivation and Family Environment Motivation had a significant and positive effect on Learning Discipline. Keywords: Learning Motivation, Family Environment, Learning Discipline